Research on electromagnetic radiation based side-channel analysis method for hardware Trojan detection - Yongkang TANG; Xing HU; Ting SU; Shaoqing LI (网络与信息安全学报)
With the globalization of the integrated circuit industry, hardware Trojan is becoming the main threat to integrated circuits.At present, the side-channel analysis which can make a good trade-off between detection ability and cost, has attracted more attention from the academia.The side-channel analysis method based on electromagnetic radiation is one of the hotspots in hardware security field.The ability evaluation of electromagnetic radiation analysis method to detect hardware Trojan was focused, and the factor that limited their detection performance was explored.The experimental results on FPGA show that the electromagnetic radiation analysis method can effectively detect hardware Trojan whose electromagnetic radiation distribution is significantly different from surrounding circuits, but it cannot be applied to hardware Trojan with complex frequency distribution of electromagnetic radiation.